Assessing Regional Integration in Africa II - United Nations (United Nations, 2006)
This report examines the effectiveness of Africa’s regional economic communities in pushing forward the regional integration agenda towards the objectives of the Abuja Treaty establishing the African Economic Community. A fully functioning African Economic Community will remove all barriers to movement of people, goods and services across the continent, thereby creating a single economic space. The report examines the critical role that institutions in general can play in achieving policy objectives, and the specific role that African institutions perform. The analysis focuses on the regional economic communities, which have been designated by the African Union as the building blocks for achieving the African Economic Community.